Phenotype Frequencies of “O” Blood Group (Rh, Kell, and MNS) among Donors in Transfusion Medicine Department of a Training Institute of Bangladesh - Bhuiyan, Mohammed Nuruzzaman; Giti, Susane; Khatun, Ayesha; Rahman, Md Moshiur; Almasud, Md Abdullah; Naher, Sharfin; Naznin, Bepasha (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Although blood transfusions can be lifesaving but it is not without risk. It is a necessity to have knowledge about the red cell antigen phenotype frequencies in a population to provide antigen-negative compatible blood to patients with multiple alloantibodies. This is the first study on extended phenotype of blood group systems in blood donors at AFIP, Dhaka. Aim: Present study is aimed to determine the antigen frequencies of “O” blood group phenotype among donors at AFIP, Dhaka. Methods: An observational study was carried out at AFIP, Dhaka from July 2019 to December 2019. A total of 40 “O” blood group donors from blood bank of AFIP were typed for D, C, c, E, e, K, k, M, N and S antigens either by adding antisera to 3-5% of donor RBCs suspension or by using Indirect Antiglobulin Test (IAT) according to manufacturer’s instruction. Coomb’s control cells, positive and negative control cells were used as quality control. Antigens and phenotype frequencies were expressed as percentages. Results: Forty (40) blood donors belonging to “O” blood group were included for extended phenotyping. D antigen was found in 100% donors, followed by e [42.5%], C [38.13%], c [11.88%], and E [7.5%] with DCe/DCe (R1R1, 55%) as the most common phenotype. k was found to be positive in 72% of donors. In the MNS system, 57.5% donors were typed as M+N+, 32.5% as M+N-, and 10% as M-N+. S-s+ was found amongst donors with 52.5% as the commonest phenotype. Conclusion: This study was conducted to provide information about the antigen frequency of a common blood group “O” in local donors to provide antigen negative compatible blood units to multi transfused alloimmunized patients. D antigen was found in 100% donors with DCe/DCe (R1R1, 55%) as the most common phenotype. J Bangladesh Coll Phys Surg 2022; 40: 171-174